Strategi Komunikasi Pemulihan Citra Positif Pt. Deltamas Menghadapi Krisis Reputasi Kepada Stakeholder - Nazwa Pratiwi Syah Putri; Muhammad Fadeli; Ratna Setyarahajoe (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the communication strategies for restoring PT. Deltamas Maju Abadi's positive image in addressing a reputation crisis in front of stakeholders. The reputation crisis was caused by internal management errors in responding to the decline in wood pallet market prices, which resulted in financial losses, delayed payments to business partners, and incorrect product deliveries to consumers. These conditions led to a decrease in stakeholder trust, especially among business partners, investors, and consumers. This study uses a qualitative descriptive method with data collection techniques through in-depth interviews and documentation. Data analysis was carried out using the Situational Crisis Communication Theory (SCCT) approach to identify the type of crisis and the communication strategies employed by the company. The results of the study indicate that the crisis experienced by PT. Deltamas Maju Abadi falls into the category of a preventable crisis, prompting the company to implement a rebuild strategy in the image recovery process. This strategy is realized through open and transparent communication, conveying apologies to stakeholders, and corrective actions such as renegotiating collaborations, changing the payment system from credit to cash, adjusting purchase prices according to market indices, and consistently fulfilling commitments. The findings show that stakeholder trust is gradually being restored, although the company's image recovery has not yet been fully achieved.